PENGARUH STRUKTUR MODAL, PROFITABILITAS, GOOD CORPORATE GOVERNANCE TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR INFRASTUKTUR - Fandy Jonathan; Maria Safitri; Vicky Oktavia; Rudi Kurniawan (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to analyze the effect of Capital Structure, Profitability, and Good Corporate Governance on stock prices. Methods: This study uses a quantitative research method, where data is obtained through the 2021 to 2023 financial reports of infrastructure and transportation sector companies listed on the Indonesia Stock Exchange. The data is processed using the IBM SPSS Statistics program. Results: The results of this study indicate that Capital Structure has a positive effect on stock prices. Profitability has a positive effect on stock prices, and Good Corporate Governance has a positive effect on stock prices, which can be seen from the multiple linear regression test with a positive role in each variable from capital structure, profitability, and institutional ownership to stock prices. Which can be concluded that capital structure, profitability, and good corporate governance have a positive effect on stock prices.. Keywords: Capital structure, Profitability, Good Corporate Governance, Stock Price